Sketching and animation using graphics strokes - Aw, Jasmin Jie Min (2012)
Traditional Chinese calligraphy and painting rely heavily on the artist's skill in executing brushstrokes. In this paper, it describes the development of a software application, namely CalliCad, which allows anyone (including unskilled users) to draw, edit, animate brushstrokes and save their works. Previous research in brushstroke modelling is investigated to build a foundation on the proposed algorithm. One of the earliest models was by Strassmann. Although the works were attractive, the computation involved was expensive. Hence, an algorithmic framework known as Disk Catmull-Rom Spline is introduced to simulate brushstrokes. For every n number of points generated by the curve, a point is selected as the control point. Next, the curve segment is computed using Catmull-Rom Spline equation. The start and end points are duplicated in order to derive a curve for the first and last segments correspondingly. Lastly, the readily available mouse device is used to input the thickness (radius) to model a stroke. The radius slowly decreases as the user draws with the mouse. After simulation of brushstrokes, the next step is animation. Keyframing is suggested here. The user creates keyframes by specifying key shapes (position and radius) of the brushstrokes as they change over time. The system then generates the in-between frames between the keyframes by recursively taking the average values of the brushstrokes’ control points attributes – (x,y) coordinates and radius. This is known as Linear Interpolation. Thereafter, the 2D interactive interface is discussed, followed by a walkthrough to get user familiarize with the application.